Avaliação de propriedades térmicas do concreto com cinza volante em fundação de aerogeradores - Gonçalves, Larissa de Freitas (2018)
Due to the large size of wind towers, the foundations are built using large volumes of concrete. In these structures, the high temperatures reached by the exothermic reaction of hydration of cement cause cracking, both by thermal energy, as well as the possibility of delayed ettringite formation. As these works have a high cost and can cause major disasters in the event of a calamity, it becomes important to undertake measures to reduce the maximum temperature of concrete, such as the use of mineral additions like fly ash. Considering this, we aimed to analyze the thermal behavior of a wind tower foundation as a result of the application of concrete produced with cement with high heat of hydration and fly ash, as an effective way to provide a suitable destination to this residue, and at the same time reduce the maximum temperature of the concrete. For this, pastes of references with cement CP III and CP IV and pastes with replacement of cement CP II F and CP V by up to 20% of fly ash were produced and tested in terms of thermomechanical behavior. In parallel, input parameters and boundary conditions for computational simulation of a wind tower foundation to check the behavior of this replacement were collected. The employment of ash, as expected, reduced the heat of hydration and the resistances of tests with the ash approached or exceeded the reference. As for the simulations, it was verified that the behavior of maximum temperatures followed the same pattern found in the heat of hydration. From the results, we concluded that it is viable to use ash substitutions in wind turbines foundations and that the mixture of CP V with 20% ash presents the best performance for this use.